STRATEGIES FOR DEVELOPING HUMAN RESOURCE CAPACITY IN EDUCATIONAL INSTITUTIONS - Mamayusupova Muattar Qosimjonovna (Bright Mind Publishing, 2025)
This article explores the theoretical and methodological foundations as well as modern strategies for developing human resource capacity in educational institutions. It analyzes approaches to enhancing teachers’ professional competencies, supporting innovative practices, integrating digital pedagogy, and implementing mentoring and coaching systems. The article also provides a scientific explanation of the criteria for assessing staff capacity and the role of monitoring and diagnostic processes in the development of educational organizations.
Keywords: Human resource capacity, professional competence, strategic management, innovative activity, mentoring, coaching, digital pedagogy, professional development, quality of education, diagnostics, monitoring